Experiment Design and Laboratory Activities on Heat Transfer to Teaching Black Principle Topic in Science to Vocational Student for Supporting Sustainable Development Goals (SDGs) - Ragadhita, Risti; Nandiyanto, Asep Bayu Dani; Riandi, R.; Wahyuni, Diah; Prajayanti, Atiek Octaria; Fiandini, Meli (Journal of Engineering Education Transformations, 2025)
This study aims to develop physics experimental learning tools on black principle material to improve vocational students’ understanding through conventional learning supported by laboratory activities. In this research, the development of the black principle experimental learning tool was carried out using a design and development (DDR) approach. To evaluate learning, this research used a one-group pre-test and post-test design. The research subjects consisted of 21 vocational students at a vocational school in the city of Cimahi, West Java. Learning is carried out through conventional methods supported by laboratory activities which consist of four stages, namely: (i) pretest; (ii) delivering learning material; (iii) laboratory activities; and (iv) post-test. Laboratory activities are carried out by observing changes in the temperature of hot substances and cold substances when hot substances are passed through cold substances. To compare students’ level of understanding before and after the learning period, pre-test and post-test data were evaluated using simple statistical calculations paired sample t-test. The results of the learning analysis show that laboratory activities can improve students’ understanding even though the improvement is categorized as moderate. Laboratory activities in the classroom are a very effective way to strengthen understanding of scientific concepts and help students link theory with practice.